The Digital Branding and Positioning Training that Aims to Increase the Number of Student Bodies of SMK Telkom 1 Medan - Moh Faidol Juddi; Martha Tri Lestari; Lusy Mukhlisiana (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The COVID-19 pandemic has limited offline activities, especially the PPDB committees of SMK Telkom 1 Medan, in achieving the target number of student bodies. Strategies for using digital technology are required to assist the PPDB committees in meeting educational targets. Hence, the PKM program initiated by the synergy of lecturers from the Faculty of Communication and Business, Telkom University, which is focused on understanding digital marketing, has been conducted in early to mid-2022 to help the PPDB committees in solving their problems. Various pieces of training to provide understanding related to concepts derived from digital marketing, one of them is digital branding, positioning, and differentiation of educational institutions training, have been given to participants online. This training was conducted in two stages. There were the delivery of material by the lecturers and a one by one coaching conducted in two-way communication, which aims to guide the participants in exploring their problems and finding effective solutions. The PKM program, which was evaluated using a survey, showed that it had answered the needs of the participants significantly in dealing with the problems they faced to increase the number of new students.